Analisis Manajemen Program Pembelajaran Bahasa Arab di Egypt Islamic Boarding and Course Pare - Alfakhaera, Arieni; Mufidah, Nuril (Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2025)
This study describes the management of Arabic language learning programs at Egypt Islamic Boarding and Course Pare, a non-formal educational institution based on boarding schools that integrates intensive courses with a boarding school system; namely how to apply management functions according to George R. Terry's theory, which includes planning, organizing, implementing, and supervising, in supporting the effectiveness of Arabic language learning programs. The method used is descriptive qualitative with data collection techniques in the form of observation, in-depth interviews, and documentation. Data analysis uses the Miles and Huberman interactive model, which consists of data reduction, data presentation, and drawing conclusions. The results of the study indicate that program planning is carried out through the preparation of an internal curriculum, a level placement system (placement test), and recruitment of teaching staff according to needs. The organization of the program can be seen from the neat institutional structure, clear division of tasks between the academic team and the dormitory management, and intensive coordination. The implementation of the program uses direct and communicative methods that are integrated with the daily activities of students in the dormitory system, creating a conducive learning environment (bi'ah lughawiyah). Program supervision is carried out through formative and summative evaluations, daily monitoring, and two-way feedback as part of quality assurance. This study shows that the application of George R. Terry's theory has proven effective in managing Arabic language learning programs in non-formal boarding school-based institutions.